Enantioselective synthesis of Iboga alkaloids and vinblastine via rearrangements of quaternary ammoniums. Issue 8 (27th May 2016) - Zhang, Yun; Xue, Yibin; Li, Gang; Yuan, Haosen; Luo, Tuoping
Abstract : We present an efficient and unified strategy for the enantioselective syntheses of various iboga alkaloids and vinblastine, involving gold-catalyzed oxidation and Stevens rearrangement. New vinblastine analogs were prepared by our 10-step synthesis. Abstract : An efficient and novel strategy for the enantioselective syntheses of various iboga alkaloids has been developed. The salient features include a gold-catalyzed oxidation of a terminal alkyne followed by cyclization, a Stevens rearrangement and a tandem sequence that combines the gold-catalyzed oxidation, cyclization and [1, 2]-shift. The catharanthine analogs provided by our approach were further converted to the vinca alkaloid vinblastine and its analogs, which confirmed the remarkable sensitivity of the cytotoxicity to the C20′ substituent of vinblastine.